Case Report: Neurally adjusted ventilatory assist as an effective rescue treatment for pulmonary interstitial emphysema in extremely low birth weight infants - Chen, Chien-Ming; Chung, Mei-Yung; Kang, Hong-Ya; Ou-Yang, Mei-Chen; Wang, Teh-Ming; Hsu, Chung-Ting (Frontiers in Pediatrics, 2024)
Pulmonary interstitial emphysema (PIE) is a complication observed in extremely low birth weight (ELBW) infants on mechanical ventilation. Despite various proposed therapeutic interventions, the success rates have shown inconsistency. Neurally adjusted ventilatory assist (NAVA) stands out as a novel respiratory support mode, offering lower pressure and tidal volume in comparison to conventional ventilation methods. In this case report, we present five ELBW infants with refractory PIE who were transitioned to NAVA ventilation. Following the switch to NAVA, all cases of PIE gradually resolved.In contrast to traditional modes, NAVA provided respiratory support with significantly lower fraction of inspired oxygen, reduced peak inspiratory pressure, diminished mean airway pressure, and decreased tidal volume within 7 days of NAVA utilization (p = 0.042, 0.043, 0.043, and 0.042, respectively). Consequently, we propose that NAVA could serve as a valuable rescue treatment for ELBW infants with PIE.